Curriculum implementation of cooperative learning models in pantun writing instruction - Komarudin, Komarudin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The Indonesian language instruction that has been applied by teachers in the classroom still relies on the practical application of conventional models, even though it is still ineffective and making students bored in the class. The purposes of this research are 1) to explain the use of cooperative learning model, especially Think-Pair-Share (henceforth TPS) in pantun (a type of old poetry) writing instruction in seventh grade to effectively improve students' abilities in writing pantun, 2) to describe the learning process of pantun writing by using TPS, and 3) to find out whether there are differences in students’ pantun writing skills before and after the use of TPS.This study used a quasi-experimental research method. Samples were taken using purposive sampling technique. The data were collected using test questions and observation sheets.  Based on the results, it can be concluded that tcount>ttable so that the application of TPS is effective in pantun writing instruction. In addition, in terms of the learning process, the use of TPS makes the students more active and the instruction more optimal than the conservative methods. Students also show improvements in writing pantun after the application of the TPS model.